The Students’ Speaking Anxiety during Pandemic Covid-19 - Bulan Anugrah; Estika Satriani; Algaziah Kurnia Difa; Haura Nadya (Universitas Pahlawan Tuanku Tambusai, 2022)
The new paradigm on the position of English in the world has shifted as now English was no longer the property of native speakers. This shifting paradigm challenge the traditional assumption of English teaching world on whether English teachers should incorporate local or target culture in their teaching materials. This is a qualitative research using critical literature review method. The topic being discussed in this article is how to incorporate local value in English language teaching materials. The issue is analysed from various perspectives, they are: world Englishes, English as International Language, culture and identity, materials development and how they shape the idea of how English teaching materials in Indonesia should be developed. In order to do that, the researchers implemented four criteria of a good ELT materials proposed by McDonough, Shaw, Masuhara, (2013). As the result of the research, we provide two suggestions. They are creating a team of book developers and providing alternatives ELT materials based on different learning styles, text genres, or even viewpoint towards an issue.